PELATIHAN KOMBINASI CORE STABILITY EXERCISE DAN ANKLE STRATEGY EXERCISE TIDAK LEBIH MENINGKATKAN KESEIMBANGAN STATIS PADA MAHASISWA S1 FISIOTERAPI STIKES ‘AISYIYAH YOGYAKARTA - Sri Yuliana; I Putu Gede Adiatmika; Muhammad Irfan; Dhofirul Fadhil Dzil Ikrom Al Hazmi (Sport and Fitness Journal, 2014)
Motor development in humans will continue to evolve from the womb to adult hood. Daily activities undertaken will increasingly severe and complex in each phase of development. The balance is a major componentin maintaining the posture of the human body to be able to straight and maintain body position. Musculoskeletal system plays an important role in maintaining the balance of the human body. Physical activity can lead to lack optimal anstatic equilibrium. The study wasaimed at Training Combination of Core Stability Exercise and Ankle Strategy Exercisedid not Increas of Core Stability Exercise For Static Balance on Students S1 Physiotherapy Stikes'Aisyiyah Yogyakarta.This study is an experimental study with Randomized Pre and Post Test Control Group Design. Samples in this study were 16 students Stikes'Aisyiyah Yogyakarta which will face semester4 of physical fitness lab and research time for 6 weeks. Divided in to two groups, group-1(core stability exercise) and group-2 (combination of corestability exercises and ankle strategy). Measurement instrument used is functional reach test are measured before treatment(0-session) and after treatment (18-session) on each subject. The result savailable in this study descriptive data samplein both groups; age20-22years, male gender and female, height 149-170 cm and weigh37-78kg. The results test stated static balance data group-1 p = 0,000 and group-2 p =0,025. Data before and after treatment 1 group-normal distribution. Then the data before and after the treatment group-2 normal distribution. Based on the compatibility test both variables in both groups, the test of hypothesis using data afte rtreatment. Variable static balance in the two groups using hypothesis independent sampel t-test p value=0,626. The conclusions available p values??>0,05. This value explained Training Combination of Core Stability Exercise and Ankle Strategy Exercise did not Increas Static Balance Of Core Stability Exercise On Students S1 Physiotherapy Stikes'Aisyiyah Yogyakarta.